2021
DOI: 10.1001/jamaoto.2021.0550
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic and Sex Representation in US-Based Clinical Trials of Hearing Loss Management in Adults

Abstract: IMPORTANCEAlthough the National Institutes of Health (NIH) mandated the inclusion and reporting of women and racial or ethnic minority groups in NIH-funded research in 1993, little is known regarding the representation of women and racial or ethnic minority groups in trials that investigate hearing loss management.OBJECTIVE To assess sex and racial/ethnic representation in US-based clinical trials of hearing loss management in an adult population.DATA SOURCES Pertinent studies were identified using search stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…50 Of those, just 5 studies had minority participation consisting of >30% of the sample. 50 Thus, research on hearing loss management failed to represent minority individuals in the United States, which weakens the generalizability of findings and the ability to discover patterns in hearing conditions among other racial and ethnic minority groups. 50 Insufficient recruitment of Black participants and other minority individuals into clinical trials leads to results that may not be inclusive of certain vulnerable populations, which limits the generalizability of findings and the development of tailored approaches for these groups.…”
Section: Discussionmentioning
confidence: 99%
“…50 Of those, just 5 studies had minority participation consisting of >30% of the sample. 50 Thus, research on hearing loss management failed to represent minority individuals in the United States, which weakens the generalizability of findings and the ability to discover patterns in hearing conditions among other racial and ethnic minority groups. 50 Insufficient recruitment of Black participants and other minority individuals into clinical trials leads to results that may not be inclusive of certain vulnerable populations, which limits the generalizability of findings and the development of tailored approaches for these groups.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review demonstrated insufficient inclusion and reporting of diverse subjects in hearing loss trials: in the 1990-2020 period, 87% of trials did not report race/ethnicity and nearly 30% did not report sex. 93 A 2021 review showed that, even with their high rates of COVID-19 vaccine hesitancy, Black individuals were still underrepresented in 62% of studies evaluating such hesitancy. 32 The Food and Drug Administration has recommended measures to enhance the diversity of clinical trial populations, such as incorporating diversity-related consideration in eligibility criteria, enrollment practices, and designs for phase III trials.…”
Section: Implications For Health Disparities Research In Otolaryngologymentioning
confidence: 99%
“…A recent review demonstrated insufficient inclusion and reporting of diverse subjects in hearing loss trials: in the 1990-2020 period, 87% of trials did not report race/ethnicity and nearly 30% did not report sex. 93 A 2021 review showed that, even with their high rates of COVID-19 vaccine hesitancy, Black individuals were still underrepresented in 62% of studies evaluating such hesitancy. 32…”
Section: Implications For Health Disparities Research In Otolaryngologymentioning
confidence: 99%
“…In studies pertaining to hearing loss management in adults that report race/ethnicity, only five studies in the past 30 years included non-White representation greater than 30% of the study population. Likewise, only half of the studies reported greater than 45% female representation ( Pittman et al 2021 ). There is a dearth of literature including racial and ethnic minorities and disadvantaged groups, and the broader generalizability of results from many existing clinical trials is limited given limitations in patient populations who have traditionally been included in hearing-related research.…”
Section: Introductionmentioning
confidence: 99%